New taeniogyrinid species of sea cucumber from the Weddell Sea (Echinodermata: Holothuroidea: Synaptida) - O’loughlin, P. Mark; Mackenzie, Melanie; Vandenspiegel, Didier; Griffiths, Huw (Zootaxa, 2015)
The case put by Alexei Smirnov in 2012 is accepted and the order name Synaptida Cuénot is adopted in place of Apodida Brandt. Two new Synaptida species are described for the Weddell Sea in Antarctica with single author O’Loughlin: Sigmodota magdarogera sp. nov. and Taeniogyrus bamberi sp. nov.. A specimen of Sigmodota magnibacula (Massin & Hétérier) is described. A key is provided for the genera and species of Taeniogyrinae that occur south of the Antarctic Convergence.